AMAP Arctic Ocean Acidification Assessment: Summary for Policy-makers. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2013)
AMAP, 2013. AMAP Arctic Ocean Acidification Assessment: Summary for Policy-makers. This document presents the Executive Summary of the 2013 Arctic Ocean Acidification (AOA) Assessment.